Envıronmental Route Of Creatıve Hope And Solıdıty - Peñaranda Galvis, Vidal Fernando, Rodríguez Miranda, Juan Pablo, Salcedo Parra, Octavio (International Journal of Advanced Science and Technology, 2020)
Breaking the laws is denying the ethical freedom of oneself. To interfere in the correct evolution of nature is to start life, to prepare to die without the consent of the eternal energy of the universe and without thinking of the common interest. Therefore, force on behalf of others is losing hope of change awaits reconciliation in value and actual paths of recover natural law and Divine sister society.